Four-days-a-week antiretroviral maintenance therapy in virologically controlled HIV-1-infected adults: the ANRS 162-4D trial - de Truchis, Pierre; Assoumou, Lambert; Landman, Roland; Mathez, Dominique; Le Dû, Damien; Bellet, Jonathan; Amat, Karine; Katlama, Christine; Gras, Guillaume; Bouchaud, Olivier; Duracinsky, Martin; Abe, Emuri; et al. (Journal of antimicrobial chemotherapy, 2018)
Intermittent treatment could improve the convenience, tolerability and cost of ART, as well as patients' quality of life. We conducted a 48 week multicentre study of a 4-days-a-week antiretroviral regimen in adults with controlled HIV-1-RNA plasma viral load (VL). Eligible patients were adults with VL < 50 copies/mL for at least 1 year on triple therapy with a ritonavir-boosted PI (PI/r) or an NNRTI. The study protocol consisted of the same regimen taken on four consecutive days per week followed by a 3 day drug interruption. The primary outcome was the proportion of participants remaining in the strategy with VL < 50 copies/mL up to week 48. The study was designed to show an observed success rate of > 90%, with a power of 87% and a 5% type 1 error. The study was registered with ClinicalTrials.gov (NCT02157311) and EudraCT (2014-000146-29). One hundred patients (82 men), median age 47 years (IQR 40-53), were included. They had been receiving ART for a median of 5.1 (IQR 2.9-9.3) years and had a median CD4 cell count of 665 (IQR 543-829) cells/mm3. The ongoing regimen included PI/r in 29 cases and NNRTI in 71 cases. At 48 weeks, 96% of participants (95% CI 90%-98%) had no failure while remaining on the 4-days-a-week regimen. Virological failure occurred in three participants, who all resumed daily treatment and became resuppressed. One participant stopped the strategy. No severe treatment-related events occurred. Antiretroviral maintenance therapy 4 days a week was effective for 48 weeks in 96% of patients, leading to potential reduction of long-term toxicities, high adherence to the antiretroviral regimen and drug cost saving.